The problem of the media presence of terrorist events: research on the interactions of visions - REZZOUG , KAMEL (Journal of Social Sciences and Humanities, 2021)
Our article seeks to study the issue of the treatment of terrorist issues by the media. In the light of the acceleration of international and Arab media institutions to cover terrorist operations, in order to inform its viewers of all the details of the events, a controversy has emerged, among media institutions which wish to give their viewers the right to complete and detailed information, and between a trend He sees this as propaganda that the media indirectly exploit to achieve the objectives of terrorist organizations by reaching public opinion. And deliver its threatening messages and dangers to its enemies. He showed a tendency which sees these coatings as a threat to the security of the individual and the stability of society, by its contribution to the germination of violence. And spread fear And between this and that, there is a broad problematic issue concerning the media dealing with the issue of terrorism, where there is a need for the media, especially Arabs, to address the issue of terrorism by:  Work to highlight the values of Islam which represent tolerance and acceptance of the other, as well as to correct the concept of jihad in public opinion  Reduce the violent scenes in the Arab satellite channels which can push to promote a culture of violence,